Environmental Sustainability, Value Re-Orientation as Panacea to Gender-Based Violence and Culture of Silence Among Adolescent Girls - Florence Adeoti Yusuf; Adesile Moshood Imran; Peter Sanjo Adewale (NUST Journal of Social Sciences and Humanities)
Gender-based violence (GBV) is an alarming global threat. It is impossible to imagine the repercussions on victims and their offspring. The detrimental African cultural customs that have supported gender-based violence are a deeply rooted problem that requires sensitive and urgent attention. Therefore, this study examined the perceived effects of environmental sustainability and value re-orientation on GBV. Data were collected from 420 respondents that were randomly selected from Osun State Nigeria. Descriptive statistics and regression analysis were used to analyse the data. Results show that the girl child is highly vulnerable to GBV while urban-rural divide and religious demographics influence rate of GBV. Environmental stressors, power imbalances, gender inequalities and social norms were identified as major causes of GBV that result in physical, reproductive, and mental health consequences for victims. Promoting environmental sustainability and value re-orientation emerges as a potential strategy to curb GBV while equitable resource management and women’s economic empowerment were identified as preventive measures. Regression analysis underscores the predictive effects of environmental sustainability (beta=.344, p<.001) and value re-orientation (beta=.384, p<001) on GBV, emphasizing the need for comprehensive interventions. Preventing GBV requires addressing the underlying causes, which include socioeconomic, cultural, and environmental issues. The fundamental causes of GBV, which include socioeconomic, cultural, and environmental problems, must be addressed in order to prevent it. For victims of gender-based violence, the Osun State Government should collaborate with non-governmental organizations and religious groups to increase their access to support services. Community leaders should implement community-based interventions, such as locking up or imprisoning those who have committed any type of GBV inside their community. The State Ministry of Youth and Women Affairs should develop a value reorientation program that challenges social norms and the silent culture.